Online Self-Conspiracy as a Challenge of Online-Mediated Communication for Social Change - Sámelová, Anna (Communication Today, 2025)
Drawing on the concepts of ‘conspiracy of silence’ and of ‘conspiracy of courtesy’ coined and developed by Joseph Ascroft, the author analyses the consequences of social media on development communication. Adopting a method of conceptual analysis of both concepts as well as using an analogy between development communication mediated by professional journalists and by online publishing laity, this investigation foregrounds the self-marginalisation of a vast chunk of the population which has emerged even in developed countries of the West and which tends to the self-conspiracy. The Western population, that imprisons itself in the national-identity (or ethnocentric) media ‘bubbles’, feels itself to be misunderstood by its own state authorities, and feels socially ignorant, illiterate, uneducated and dependent, in short marginalised in questions of multiculturalism and self-identity. As a result, development communication in the field of social change must take a twofold effort – to overcome the barriers of silent mistrust or of uncooperative courtesy firstly ‘inside the Western society’ facing media ‘bubbles’ as well as ‘outside’ facing real conspiracy of silence or courtesy. The aim of this study is clarifying the role of development communication in processes of social change in the online era and assessing its ability to facilitate active participation of (self-) marginalised groups at all stages of the development process.